Aqueous flow battery based on iron-based metal organic complex

By using Fe(EDTMP) complex as the electrolyte in an aqueous all-iron flow battery, the phosphate groups and Fe3+ ions form a stable coordination bond, the problems of metal iron deposition, dendrite growth and hydrogen evolution reaction in the battery are solved, and the stability and cycling performance of the battery are significantly improved, and are suitable for large-scale energy storage applications.

CN119864461APending Publication Date: 2025-04-22NANJING UNIV TIANCHANG NEW MATERIALS & ENERGY TECH R&D CENT +4
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510094042.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

Water-based all-iron flow batteries face problems such as metal iron deposition, dendrite growth and hydrogen evolution reaction, resulting in low solubility of electrochemically active materials and poor battery cycle stability.

Method used

Fe(EDTMP) complex is used as the electrolyte to form a stable coordination bond with Fe3+ ions through phosphate groups, so as to improve solubility and electrochemical stability, and inhibit the occurrence of side reactions.

Benefits of technology

It significantly improves the electrochemical stability, cycling performance and economy of the battery, extends the long-term stability of the battery, and is suitable for large-scale energy storage applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119864461A_ABST
    Figure CN119864461A_ABST
Patent Text Reader

Abstract

The invention relates to an aqueous flow battery based on an iron-based metal organic complex. The complex adopts ethylenediamine tetramethylenephosphonic acid (EDTMP) as a ligand, and forms a stable coordination compound with iron ions (Fe < 3 + >), so that the solubility and the electrochemical stability of an electrochemical active substance are remarkably improved. By means of the strong electron donating ability of a phosphate group, a multi-tooth coordination structure and Fe (EDTMP), side reactions such as hydrogen evolution reaction, iron dendrite growth and transmembrane pollution are effectively inhibited. Experimental results show that the aqueous flow battery based on the Fe (EDTMP) complex has excellent discharge capacity and high energy efficiency, and the capacity retention ratio is still very high after 1000 times of charge-discharge cycles. The research provides a new solution for improving the performance of the aqueous flow battery, verifies the superiority of Fe (EDTMP) as an iron-based complex electrolyte, and shows a wide application prospect of Fe (EDTMP).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electrochemical energy storage, and specifically discloses an aqueous liquid flow battery based on an iron-based metal organic complex. Background Art

[0002] With the increasing demand for renewable energy and the advancement of energy storage technology, flow batteries, as an important energy storage technology, have received widespread attention. Aqueous flow batteries have become one of the most promising energy storage technologies due to their high safety, good environmental friendliness and low cost. However, aqueous flow batteries face challenges such as low solubility of electrochemically active materials, poor battery cycle stability and hydrogen evolution reaction, which seriously limit their widespread application. As an emerging technology, all-iron flow batteries use iron ions as active materials, with lower cost and higher resource availability. However, in actual application, aqueous all-iron flow batteries still face problems such as metallic iron deposition, dendrite growth and hydrogen evolution reaction.

[0003] In order to improve the performance of aqueous all-iron flow batteries, this study proposed a new Fe(EDTMP) complex and applied it to the negative electrode of neutral aqueous all-iron flow batteries. Through the strong coordination between phosphate groups and iron ions, the Fe(EDTMP) complex can significantly improve the solubility and electrochemical stability, effectively inhibit the occurrence of side reactions, and significantly improve the battery performance and cycle stability. Summary of the invention

[0004] The object of the present invention is to provide an aqueous liquid flow battery based on an iron-based metal organic complex, which exhibits excellent electrochemical performance, stability and cycle performance under neutral pH conditions.

[0005] The present invention discloses an aqueous liquid flow battery based on an iron-based metal organic complex, wherein the electrolyte of the aqueous liquid flow battery is an aqueous solution of an Fe(EDTMP) complex, wherein the complex binds to Fe via a phosphate group. 3+ The ions form stable coordination bonds.

[0006] Furthermore, the Fe(EDTMP) complex uses ethylenediaminetetramethylenephosphonic acid as a ligand to form a hexacoordinate structure.

[0007] Furthermore, the preparation method of the Fe(EDTMP) complex comprises reacting ethylenediaminetetramethylenephosphonic acid with iron ions under neutral pH conditions to form the Fe(EDTMP) complex.

[0008] Furthermore, the preparation method of the Fe(EDTMP) complex comprises the following specific steps:

[0009] Step 1: Disperse ethylenediaminetetramethylenephosphonic acid (EDTMP) in deionized water, add sodium carbonate and stir until EDTMP is completely dissolved to obtain a clear transparent solution containing ethylenediaminetetramethylenephosphonic acid and sodium carbonate, and the stirring time is 2-4 hours;

[0010] Step 2: dissolving ferric chloride heptahydrate in deionized water, and adding dropwise to the solution in step 1, during which the pH value of the solution was detected. When the pH reached 7, a yellow-brown clear and transparent solution was formed;

[0011] Step 3: The above solution is concentrated by rotary evaporation to obtain a Fe(EDTMP) complex solution.

[0012] Further, in step 1, the molar ratio of EDTMP to Na2CO3 is 1:(4-5);

[0013] Further, in step 2, the molar ratio of ferric chloride heptahydrate to EDTMP is 1:(1-1.5);

[0014] Further, the stirring time in step 1 is 2-4 hours, and the stirring time in step 2 is 24-30 hours;

[0015] Further, the rotary evaporation in step 3 is performed at 70°C;

[0016] Further, the aqueous flow battery also includes a 1.0M NaCl aqueous solution;

[0017] Furthermore, the solubility of the Fe(EDTMP) complex under neutral pH conditions is 1.47M.

[0018] Furthermore, the aqueous liquid flow battery includes a 1.0M NaCl aqueous solution as a supporting electrolyte, and the capacity of the aqueous liquid flow battery at a concentration of 1.0M and a current density of 100mAcm-2 is 22.97Ah L-1, and the energy efficiency reaches 86.2%.

[0019] Furthermore, the discharge capacity of the aqueous flow battery is retained at a rate of up to 99.9% after 1000 charge and discharge cycles.

[0020] The aqueous liquid flow battery based on an iron-based metal organic complex proposed by the present invention has the following beneficial effects:

[0021] 1. The present invention uses the aqueous solution of the Fe(EDTMP) complex as an electrolyte in an aqueous flow battery, which significantly improves the electrochemical stability, cycle performance and economy of the battery. 3+The strong coordination between ions effectively improves the solubility of the battery and inhibits side reactions such as hydrogen evolution reaction, iron dendrite growth and transmembrane contamination, thereby significantly improving the long-term stability of the battery. This technology has low cost and high efficiency, is suitable for large-scale energy storage applications, and lays a solid foundation for the commercial application of flow batteries in the field of renewable energy storage;

[0022] 2. The core of the technical solution of the present invention is to use an aqueous solution of a Fe(EDTMP) complex as an electrolyte. The Fe(EDTMP) complex is composed of Fe 3+ It is composed of EDTMP and has high solubility, which can increase the amount of ions dissolved in the battery, improve ion concentration and conductivity; it has excellent ionic conductivity, can provide higher ion transmission rate, and enhance the power output and charge and discharge rate of the battery; it has excellent chemical stability, can effectively inhibit the water decomposition reaction, and improve battery stability and cycle life; its design flexibility enables it to meet specific application requirements through reasonable structural design and synthesis regulation;

[0023] 3. The reaction of the present invention uses FeCl3·6H2O and H8EDTMP as raw materials, and Na2CO3 is used to adjust the pH value. The prepared aqueous flow battery has a concentration of 1.0M and a current of 100 mA cm -2 After 1000 cycles at the current density, its capacity is 22.97Ah L -1 , capacity retention rate reaches 99.5%, energy efficiency is 86.2%, and coulomb efficiency is 99.9% BRIEF DESCRIPTION OF THE DRAWINGS

[0024] The accompanying drawings are used to provide further explanation of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings:

[0025] Figure 1 is a spectral characterization diagram of the complex in Example 1 of the present invention;

[0026] Figure 2 is the test result of Test 1 of the present invention;

[0027] Figure 3 are the test results of Tests 2-4 of the present invention;

[0028] Figure 4 It is the test result of the energy storage performance of the aqueous liquid flow battery of the present invention. DETAILED DESCRIPTION

[0029] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.

[0030] Unless otherwise specified, the examples and comparative examples are parallel tests with the same components, component contents, preparation steps and preparation parameters. The experimental methods in the following examples are conventional methods unless otherwise specified. The experimental materials used in the following examples are purchased from commercial channels unless otherwise specified.

[0031] Unless otherwise stated, all reagents were used as received without further purification.

[0032] Both the positive electrode and the negative electrode include electrodes, wherein the electrodes include one or more of carbon felt, carbon paper, carbon cloth, carbon black, activated carbon fiber, activated carbon particles, graphene, graphite felt, and glassy carbon materials. The positive and negative electrodes of Example 1 are carbon felt, and the electrolytic cell is a graphite plate, which has excellent fluid mechanics and chemical tolerance to achieve efficient electrolyte flow and reaction, and the diaphragm is a perfluorosulfonic acid membrane (Nafion membrane). The electrolyte includes a positive electrode electrolyte and a negative electrode electrolyte; wherein the positive electrode electrolyte includes one of Na4[Fe(Dcbpy)2(CN)2](or K4[Fe(Dcbpy)2(CN)2]), Na4[Fe(CN)6](or K4[Fe(CN)6]), and the negative electrode electrolyte is Fe(EDTMP).

[0033] In the present technical solution, the Fe(EDTMP) concentration in the low-concentration battery system is 0.1 M, and the Fe(EDTMP) concentration in the high-concentration battery system is 1.0 M. In addition, a 1.0 M NaCl aqueous solution is added as a supporting electrolyte.

[0034] Embodiment 1:

[0035] An aqueous liquid flow battery based on an iron-based metal organic complex is prepared by using a Fe(EDTMP) complex as a negative electrode electrolyte.

[0036] The preparation method of Fe(EDTMP) complex comprises the following steps:

[0037] Step 1: Disperse 2.18 g of ethylenediaminetetramethylenephosphonic acid in 10 ml of deionized water, add 2.54 g of sodium carbonate and stir for 2 hours to form a clear transparent solution;

[0038] Step 2: Dissolve 1.35 g of ferric chloride heptahydrate in 5 ml of deionized water, add dropwise to the above clear transparent solution, stir for 24 hours to obtain a yellow-brown clear transparent solution, and detect the pH value of the yellow-brown clear transparent solution, which is 7;

[0039] Step 3: The above solution was rotary evaporated at 70°C to a specific volume to obtain a Fe(EDTMP) solution.

[0040] During this experiment, Fe 3+ The Fe(EDTMP) complex is formed by coordination reaction with EDTMP at room temperature, and then a Fe(EDTMP) solution is obtained by rotary evaporation.

[0041] Example 2

[0042] The preparation method of Fe(EDTMP) complex comprises the following steps:

[0043] Step 1: Disperse ethylenediaminetetramethylenephosphonic acid in deionized water, add sodium carbonate and stir for 3 hours to form a clear and transparent solution;

[0044] Step 2: dissolving ferric chloride heptahydrate in deionized water, adding dropwise to the above solution, stirring for 26 hours to obtain a yellow-brown clear transparent solution, and detecting the pH value of the yellow-brown clear transparent solution, which is 7;

[0045] Step 3: The above solution was rotary evaporated at 70°C to obtain a Fe(EDTMP) solution.

[0046] In this embodiment, the molar ratio of EDTMP to Na2CO3 is 1:5, Fe 3+ The molar ratio with EDTMP is 1:1.2.

[0047] Example 3

[0048] The preparation method of Fe(EDTMP) complex comprises the following steps:

[0049] Step 1: Disperse ethylenediaminetetramethylenephosphonic acid in deionized water, add sodium carbonate and stir for 4 hours to form a clear and transparent solution;

[0050] Step 2: dissolving ferric chloride heptahydrate in deionized water, adding dropwise to the above solution, stirring for 30 hours to obtain a yellow-brown clear transparent solution, and detecting the pH value of the yellow-brown clear transparent solution, which is 7;

[0051] Step 3: The above solution was rotary evaporated at 70°C to obtain a Fe(EDTMP) solution.

[0052] In this embodiment, the molar ratio of EDTMP to Na2CO3 is 1:4, Fe3+ The molar ratio with EDTMP is 1:1.5.

[0053] Performance Testing

[0054] Perform X-ray Absorption Fine Structure (XAFS) testing, Figure 1 a is the k3-weighted iron K-edge EXAFS spectrum after Fourier transformation, which comes from Fe(EDTMP) and reference samples (iron foil and Fe2O3), respectively. Figure 1 b- Figure 1 d shows the EXAFS fitting curves of iron foil, Fe2O3 and Fe(EDTMP) after Fourier transformation. Figure 1 a- Figure 1 The structural characterization in d proves that Fe(EDTMP) has a hexacoordinated structure.

[0055] Test 1. Solubility test of Fe(EDTMP) complex: At room temperature, the aqueous solution of Fe(EDTMP) complex was rotary evaporated until a precipitate was formed in the solution to obtain a saturated solution of Fe(EDTMP) electrolyte; the saturated solution was then diluted, and the concentration of Fe(EDTMP) electrolyte in the diluted solution was measured using an ultraviolet spectrophotometer, and the solubility of the Fe(EDTMP) complex in water was calculated based on the dilution factor.

[0056] Test 2: Redox performance test: A standard three-electrode device was used to perform cyclic voltammetry analysis on the redox properties of the electrolyte, using a 50mm diameter glassy carbon electrode as the working electrode, a platinum wire electrode as the counter electrode, and a saturated Ag / AgCl electrode as the reference electrode.

[0057] Test 3: Diffusion coefficient test: Cyclic voltammetry was performed on the electrolyte at different scan rates using a standard three-electrode apparatus, and the diffusion coefficient was calculated using the Randles-Sevcik equation.

[0058] Test 4: Electron transfer rate constant test: Cyclic voltammetry tests were performed on the electrolyte at different scan rates using a standard three-electrode apparatus, and the electron transfer rate constant was calculated using the Nicholson equation.

[0059] See also Figure 2 a- Figure 2 As shown in b, Figure 2 a is the UV absorption spectra of Fe(EDTMP) solutions with different concentrations. Figure 2 b is the concentration test calculation of Fe(EDTMP); the calculation results show that the solubility of the coordinated Fe(EDTMP) complex reaches 1.47M.

[0060] See also Figure 3 a- Figure 3As shown in d, Figure 3 a and Figure 3 b is the calculated diffusion coefficient of Fe(EDTMP), Figure 3 c and Figure 3 d is the calculated electron transfer rate constant of Fe(EDTMP); the calculation results show that Fe(EDTMP) has excellent kinetic performance.

[0061] The energy storage performance of the aqueous flow battery was tested as follows:

[0062] The battery performance test was carried out using the LAND CT2001A battery test system and a standard flow battery module, with Na4[Fe(Dcbpy)2(CN)2] as the positive electrolyte; the area used was 6×6cm 2 The anion exchange membrane separates the cathode and anolyte; the reaction area is based on the area of ​​the graphite felt electrode (5 cm 2 ); the electrolyte is pumped through a peristaltic pump (BT100-2J) at a rate of 70 ML min -1 The flow rate circulates between the battery and the tank.

[0063] Test a. Battery rate performance test: Use LAND CT2001A battery test system to test 0.1M concentration batteries at 20, 40, 60, 80, 100 mA cm -2 The constant current charge and discharge test was carried out at a current density of 1.

[0064] Test b. Battery constant current charge and discharge stability test: Using the LAND CT2001A battery test system, constant current charge and discharge tests were performed on batteries of different concentrations at current densities of 60 and 100 mA cm-2.

[0065] like Figure 4 a- Figure 4 As shown in d, Figure 4 a is the rate performance of the aqueous liquid flow battery based on the Fe(EDTMP) complex of Example 1, Figure 4 b is the charge and discharge curves of the aqueous liquid flow battery based on the Fe(EDTMP) complex of Example 1 at different current densities, Figure 4 c is the aqueous liquid flow battery based on the Fe(EDTMP) complex of Example 1 at a concentration of 0.1 M at 60 mA cm -2 Cyclic test at current density, Figure 4 d is the aqueous liquid flow battery based on the Fe(EDTMP) complex of Example 1 at 100 mA cm -2 Cyclic test under current density; Through constant current cycling stability test, it was found that the aqueous liquid flow battery based on the Fe(EDTMP) complex of Example 1 has excellent stability during the charge and discharge process.

[0066] The capacity of the aqueous flow battery based on the 1.0 M Fe(EDTMP) complex of Example 1 after 1000 cycles was 22.97 Ah L -1 , capacity retention rate reaches 99.5%, energy efficiency is 86.2%, and coulomb efficiency is 99.9%;

[0067] At 60mA cm -2 At the current density of 0.1 M, the capacity of the aqueous flow battery based on the Fe(EDTMP) complex of Example 1 after 1000 cycles was 2.33 Ah L -1 , capacity retention rate is 99.7%, energy efficiency is 87.6%, and coulombic efficiency is 99.9%;

[0068] These results indicate that the Fe(EDTMP) complex has high solubility, high volumetric capacity and good cycling stability as anode materials for aqueous flow batteries.

[0069] In summary, the present invention proposes an Fe(EDTMP) complex as an electrolyte for an aqueous liquid flow battery, which has the advantages of high solubility, high volumetric capacity, good cycle stability, adjustability, customizability and environmental friendliness; high solubility improves ion concentration and conductivity; high volumetric capacity enables it to store more charge; good cycle stability ensures long-term stable operation; adjustability and customizability enable it to adapt to different battery system requirements; environmental friendliness makes it more sustainable and environmentally friendly; these advantages make the Fe(EDTMP) complex a candidate material with potential for application in large-scale energy storage systems and liquid flow battery technology.

[0070] The Fe(EDTMP) complex aqueous flow battery based on the above design has strong electron donation ability and stable multidentate coordination structure with Fe 3+ The formation of a strong coordination bond significantly improves the solubility, electrochemical stability and resistance to side reactions of the complex. In the battery performance test, the all-iron liquid flow battery based on Fe(EDTMP) exhibited excellent rate performance, high power output and long cycle stability. Under high current density conditions, the battery can still maintain high capacity and high efficiency.

[0071] This invention not only provides a new idea for the optimal design of neutral aqueous flow batteries, but also lays a theoretical and technical foundation for the development of new iron-based complex electrolyte systems. In the future, the research and application of Fe(EDTMP) is expected to promote the widespread application of flow batteries in the field of renewable energy storage and help build a greener and more sustainable energy system.

[0072] The specific embodiments of the present invention are described in detail above, but they are only examples, and the present invention is not limited to the specific embodiments described above. For those skilled in the art, any equivalent modifications and substitutions made to the present invention are also within the scope of the present invention. Therefore, the equalization changes and modifications made without departing from the spirit and scope of the present invention should be included in the scope of the present invention.

Claims

1. An aqueous liquid flow battery based on an iron-based metal organic complex, characterized in that: The electrolyte of the aqueous flow battery is an aqueous solution of a Fe(EDTMP) complex, and the complex forms a stable coordination bond with Fe3+ ions through a phosphate group.

2. The aqueous flow battery according to claim 1, characterized in that: The Fe(EDTMP) complex uses ethylenediaminetetramethylenephosphonic acid as a ligand to form a hexacoordinate structure.

3. The aqueous flow battery according to claim 1, characterized in that: The preparation method of the Fe(EDTMP) complex comprises reacting ethylenediaminetetramethylenephosphonic acid with iron ions under neutral pH conditions to form the Fe(EDTMP) complex.

4. The aqueous liquid flow battery according to claim 3, characterized in that: The molar ratio of the iron ion to ethylenediaminetetramethylenephosphonic acid is 1:(1-1.5).

5. The aqueous liquid flow battery according to claim 3, characterized in that: The solubility of the Fe(EDTMP) complex is 1.47M under neutral pH conditions.

6. The aqueous liquid flow battery according to claim 1, characterized in that: The preparation method of the Fe(EDTMP) complex comprises dispersing ethylenediaminetetramethylenephosphonic acid in deionized water, adding sodium carbonate and stirring to obtain a clear transparent solution containing ethylenediaminetetramethylenephosphonic acid and sodium carbonate, wherein the stirring time is 2-4 hours, and the molar ratio of EDTMP to sodium carbonate is 1:(4-5).

7. The aqueous flow battery according to claim 6, characterized in that: The preparation method of the Fe(EDTMP) complex comprises dissolving ferric chloride heptahydrate in deionized water, adding the solution to a clear transparent solution containing ethylenediaminetetramethylenephosphonic acid and sodium carbonate, and stirring the solution to obtain a yellow-brown clear transparent solution, wherein the stirring time is 24-30 hours.

8. The aqueous flow battery according to claim 7, characterized in that: The preparation method of the Fe(EDTMP) complex further comprises rotary evaporating the yellow-brown clear and transparent solution to obtain a Fe(EDTMP) complex solution, wherein the rotary evaporation temperature is 70°C.

9. The aqueous liquid flow battery according to claim 1, characterized in that: The aqueous flow battery uses a 1.0M NaCl aqueous solution as the supporting electrolyte, and after 1000 cycles at a concentration of 1.0M and a current density of 100mAcm-2, its capacity is 22.97Ah L-1, the capacity retention rate reaches 99.5%, the energy efficiency is 86.2%, and the coulombic efficiency is 99.9%.

10. The aqueous flow battery according to claim 1, characterized in that: At a current density of 60 mA cm-2, based on the 0.1 M Fe(EDTMP) complex in Example 1, the aqueous liquid flow battery has a capacity of 2.33 Ah L-1 after 1000 cycles, a capacity retention rate of 99.7%, an energy efficiency of 87.6%, and a coulombic efficiency of 99.9%.